Interactive Multimedia-Based Arabic Language Learning: A Systematic Literature Review (Jurnal Sustainable, 2024)
This paper aims to describe the types of interactive multimedia that can be used in Arabic language learning and the effectiveness of using interactive multimedia in Arabic language learning. The research method employed is the Systematic Literature Review, which includes literature search, application of inclusion and exclusion criteria, and quality assessment of articles. The database used in this study is dimensions.ai. The research findings indicate that there are 20 types of interactive multimedia that can be used in Arabic language learning, namely:  Adobe Flash, Visual Learning Multimedia, Android Multimedia, Canva Multimedia, Interactive Animated Videos, 3D Augmented Reality, Lecture Maker, Flash Mx, Mondly, Lectora Inspire, Wordwall Application, Plotagon Studio, Youtube, Educandy Platform, Interactive E-Modul, Powerpoint Ispring Presenter, Articulate   Storyline 3, Android-Based Learning Media' Smart Tree: We Can', Media Quizizz, and Flash Macro Media. These interactive multimedia tools have proven effective in enhancing students' interest, learning motivation, speaking skills, vocabulary mastery, listening ability, text comprehension, and understanding of Arabic grammar in Arabic language learning. The results of this study can be used as a reference in selecting Arabic language learning multimedia that aligns with the hoped learning objectives.